SP1-induced lncRNA ZFPM2 antisense RNA 1 (ZFPM2-AS1) aggravates glioma progression via the miR-515-5p/Superoxide dismutase 2 (SOD2) axis. Issue 1 (1st January 2021) - Zhang, Yaxuan; Zhang, Yin; Wang, Sen; Li, Qingquan; Cao, Boqiang; Huang, Baosheng; Wang, Tianlu; Guo, Ruijuan; Liu, Ning
ABSTRACT: Glioma is a common life-threatening tumor with high malignancy and high invasiveness. LncRNA ZFPM2 antisense RNA 1 (ZFPM2-AS1) was confirmed to be implicated in numerous tumors, while its biological function and mechanism have not been thoroughly understood in glioma. The gene expression was measured by RT-qPCR. Cell proliferation, cell cycle, and cell apoptosis of glioma cells were validated by CCK-8, colony formation, flow cytometry and TUNEL assays. The effect of ZFPM2-AS1 on tumor growth was verified by in vivo assay. The exploration on ZFPM2-AS1-mediated mechanism was carried out via ChIP, luciferase reporter, and RIP assays. In the present study, ZFPM2-AS1 was demonstrated as a highly-expressed lncRNA in glioma tissues and cells. ZFPM2-AS1 silencing suppressed cell proliferation and cell cycle, but facilitated cell apoptosis. In addition, the inhibitive effect of silenced ZFPM2-AS1 was also observed in tumor growth. Furthermore, we found that SP1 interacted with ZFPM2-AS1 promoter to transcriptionally activate ZFPM2-AS1 expression. Moreover, ZFPM2-AS1 was identified as a competing endogenous RNA (ceRNA) for miR-515-5p to target SOD2. Rescue assays verified that SOD2 overexpression partially abolished the suppressive impact of ZFPM2-AS1 silencing on glioma cell growth. In conclusion, this study corroborated the regulatory mechanism of SP1/ZFPM2-AS1/miR-515-5p/SOD2 axis in glioma, indicating that targeting ZFPM2-AS1 might be an effective way to treat glioma.